2018
DOI: 10.1177/1065912918806048
|View full text |Cite
|
Sign up to set email alerts
|

Who Represents Me? Race, Gender, Partisan Congruence, and Representational Alternatives in a Polarized America

Abstract: The belief among citizens that their views are represented is essential to the legitimacy of American democracy, but few studies have explicitly examined which political actors Americans feel best represent them. Using data from the 2006 Cooperative Congressional Election Study, we ask new questions about whether respondents who share a partisan, racial, or gender identification with their members of Congress (MCs) feel those members best represent them. Although the framers designed the House so that individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…Given these benefits, what accounts for varied levels of support for increasing diversity in representation? Research finds that individuals are more likely to prefer identity congruence with elected officials (English et al, 2019; Gershon et al, 2019; Philpot & Walton, 2007; Rosenthal, 1995; Sanbonmatsu, 2003; Tate, 1993;). A 2018 Pew study found that women were 21 percentage points more likely than men to believe there are too few women in political office (69% vs. 48%) (Horowitz et al, 2018, see also Gallup News Service, 2001).…”
Section: Attitudes Toward Descriptive Representationmentioning
confidence: 99%
See 2 more Smart Citations
“…Given these benefits, what accounts for varied levels of support for increasing diversity in representation? Research finds that individuals are more likely to prefer identity congruence with elected officials (English et al, 2019; Gershon et al, 2019; Philpot & Walton, 2007; Rosenthal, 1995; Sanbonmatsu, 2003; Tate, 1993;). A 2018 Pew study found that women were 21 percentage points more likely than men to believe there are too few women in political office (69% vs. 48%) (Horowitz et al, 2018, see also Gallup News Service, 2001).…”
Section: Attitudes Toward Descriptive Representationmentioning
confidence: 99%
“…A 2018 Pew study found that women were 21 percentage points more likely than men to believe there are too few women in political office (69% vs. 48%) (Horowitz et al, 2018, see also Gallup News Service, 2001). Similarly, across all racial/ethnic groups, including white Americans, individuals are thought to prefer representatives with whom they share a racial/ethnic identification (Casellas & Wallace, 2015; English et al, 2019; Schildkraut, 2017).…”
Section: Attitudes Toward Descriptive Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…Partisanship also shapes the output of politics: Where quotas (and in particular, party quotas) have now existed long enough to evaluate their effects, evidence is accumulating that changes in legislative demographics affect substantive representation (Bratton, Haynie, & Reingold, ; Clayton & Zetterberg, ; Franceschet & Piscopo, ). Partisanship also shapes diverse constituents' perceptions of their elected representatives and perceived the trustworthiness of democratic systems (Barnes & Beaulieu, ; English, Pearson, & Strolovitch, ). These bodies of research lead the way in bringing partisanship into intersectional approaches to gender and politics.…”
Section: Bringing Partisanship Into Intersectionalitymentioning
confidence: 99%
“…According to , symbolic representation concerns affective beliefs about whether or not people feel that their interests and views are represented in parliament. Future research should therefore go beyond merely analyzing the extent of male MP's engagement in women's substantive representation, and should explore the question of whether or not women in the population feel represented if men speak on their behalf, or if they instead believe that their views and interests are more thoroughly represented by female MPs (English, Pearson and Strolovitch 2019). This question could be analyzed in several experiments in which respondents could be presented with a vignette including, for example, a report on a newly enacted women-specific policy in parliament.…”
Section: Directions For Future Researchmentioning
confidence: 99%